PENDIDIKAN DAN KEKAYAAN MASA DEPAN (FUTURE WEALTH) DI ERA GLOBAL - Suwarjo Suwarjo (Paradigma, 2006)
Individual behavior will never be detached from its cultural contexts. Most (if not all) of the behaviors carried out by an individual are formed through the long process of learning in the place or environment where he/she grows up and lives. Models of behavior shown by the members of a community will also influence an individual behavior in that community. Values, norms, and habits in a certain culture will also affect parenting style. Besides, individuals also do some contacts with their cultural environment. In its interaction, an individual will manage to fit him/herself with the culture by means of “assimilating and/or adapting” micro cultures to macro culture. For this reason, we can understand a client thoroughly, perform appropriate assessments, and give interventions correctly, if we are able to understand the client in accordance with his/her cultural context. Concerning with this, Pederson affirms that “Since all behaviors are learned and displayed in cultural context, accurate assessment, meaningful understanding and appropriate interventions are done from the perspective of client’s cultural context” . Implications of Pederson’s statement towards counseling processes are: (a) In a counseling process, counselor needs to be aware that there is a process of cultural contact between client’s culture and counselor’s culture, which will be potential for the emergence of cultural biases (even though the client and the counselor both come from the same ethnic and culture). Therefore, a counselor should not be “cultural blind”; a counselor must be “cultural aware”; (b) Cultural differences will cause different perceptions, mind-sets, attitudes and values, and different ways of expressions in overt behavior as well. Therefore, a counselor needs to be aware of the biases emerging from the theory, technique, and approach used in counseling; (c) The use of psychological measuring tools (tests) in counseling as one effort for counselor to comprehend the client also needs attention. Have the measuring tools been constructed in accordance with the surrounding culture of the client? Have the emergence of cultural biases been anticipated as a threat to the validity of measuring tools? Counselors need to be “critical and wise” towards the using and meaning of results of the measuring tools. Measuring tools (tests) can be placed as one way, not the only way to achieve the objectives. Counseling process as one form of counseling services to clients, naturally, constitutes an encounter of cultures, i.e. the client’s culture and the counselor’s culture. Effective counseling requires counselors to be aware and sensitive of cultural differences.Key words : cross cultural counseling, cultural sensitivity